THE CONCEPT AND DEFINITION OF REGIONAL BOOK (AN EXAMPLE OF SAMOGITIAN BOOK) - PETREIKIS, TOMAS (Knygotyra, 2015)
The Samogitian book is a relevant part of the regional culture history. In this article, the regional book is shown as a publishing product of the local communities which met their demands. Samogitia’s historical development is analysed in more detail, whilst its clarifications are essential when determining the spread of regional book culture. The status and territorial delineation of Samogitia had been changing, thus three regional stages are distinguished: 1) the Great Duchy of Lithuania (1795), 2) tsarist Russia (1975–1917) and 3) Independent Lithuania (1918–1944). The precise choice of time and space allows us to name the Samogitian press as a production which is familiar from the data of publishing and printing. With reference to this principle, the multilingual layers of printed and handwritten heritage of the region are covered. Regional book in the sense of author and language is variegated. Its creators were culturally active members of local communities, which met the needs of themselves and of other local inhabitants. Besides Lithuanian book, attention is drawn also to Latin, Polish, Russian, French, Jewish and German press production. Local handwritten heritage and handwritten books are integrated into the analysis of regional book as the distinctive part of regional book culture.The Samogitian ethnic book, witten in its peculiar dialect, is recognized as a quite independent and at the same time integral part of Samogitian book. Samogitian book, which had its upspring late in the 17th century, had very strong positions in the culture of Great Lithuania in the 19th century due to the Lituanistic movement. It decreased in the period of generating Lithuanian appellative language, although cultured Samogitians had been recovering it during all the first part of the 20th century. The Samogitian book underwent the patterns that are common and appropriate only for this region and which influenced the complicated situation of publishing and the general state of book culture. Referring to this concept of regional book, the Samogitian book is conceived as a consistent part of the Great Lithuania’s book history.
Keywords: ...